EFEKTIFITAS PENGGUNAAN FASILITAS JEMBATAN PENYEBERANGAN ORANG (JPO) (Studi Kasus Pada Fasilitas Jembatan Penyeberangan Orang di Kota Bandar Lampung) - Wildan, Irsyad; Damayantie, Anita (SOCIOLOGIE, 2013)
This research was done to know about how the effectifity of utilization Person Overpass Facility exist at Bandarlampung City. As we know that the increasing of transportation vehicle volumes cause protocol streets become more density in Bandarlampung City. Of course this matter cause the road jogger be difficult to across the road especially in busy times like in the morning when people goint to work place and going to school or in the evening when they going home. Moving of include their moving when they tracing the road, across road and narrow ones. As common happened in every big cities, this matter happenend because of economy development demand, trading, and the ease of the people to reach the social service, so public facilities like hotel, shopping centre, etc. tend to grouping at certain area. Beside that, because of the location of a building with another scattered to the whole areas, so foot jogger should across the traffic to reach their destination. But, the existence of foot jogger in certain level often cause the big conflict with the vehicle`s current until cause the delaying of the traffic and height degree of accident number.Keywords: Effectiveness, people crossing bridge